Unveiling the nexus: A bibliometric analysis of nano plastic’s health impact - Alok Singh; Vanisree Ramanathan; Ujjwal Kumar; Shailesh Tripathi; Sheikh Mohd Saleem; Deep Shikha; Poonam Kushwaha; Sudip Bhattacharya (Journal of Education and Health Promotion)
Plastics are integral to daily life due to their flexibility, durability, low viscosity, and poor conductivity. However, UV exposure, weathering, and biodegradation fragment plastics into microplastics and nano plastics, forming a heterogeneous mix categorized as large microplastics (5 mm to 1 mm), small microplastics (1 mm to 1 μm), and nano plastics (<1 μm). Concerns over the health impacts of micro and nano plastic (MNP) pollution have spurred extensive research, revealing increased disease susceptibility. Recent studies, analyzed using tools like Biblioshiny and Vos viewer software, have focused on authorship, journal sources, geographic origins, and emerging trends in MNP research. Data from the SCOPUS database (January 1, 2015 to January 3, 2024) analyzed via Biblioshiny and Microsoft Excel revealed 478 articles, with a steady annual increase in publications and references, highlighting growing interest in nanoplastics’ health impacts. China leads in publications and collaborations, with eight of the top ten contributing institutions located there, alongside Spain and Serbia. Chinese authors also dominate the top ten published papers in leading journals, five of which are prominent in Environmental Science. This study presents the first visual metametrological analysis of the connection between nanoplastics and human health using bibliometric techniques. By examining global research on nanoplastics’ health implications, we can better understand the current research landscape and set priorities for future studies.